Financial Feasibility Study of Arabica Coffee: A Case Study in Poetete Village, Ermera District, Timor Leste - Mateus Maia de Jesus; Lya Aklimawat; Budi Setiawan; Djoko Koestiono (Indonesian Coffee and Cocoa Research Institute, 2017)
Coffee is not only the main export product in Timor Leste, but also a source of income for farmer household. The importance of coffee for Timor Leste community should be developed through market oriented farm management on coffee farming. The aim of this research was to analyze financial feasibility of Arabica coffee farming at farmer level; analyze sensitivity of coffee farming toward change in coffee productivity and price; and analyze correlation between productivity with socio-economic characteristics of farmers. This research was carried out at Poetete Village, Ermera Sub-district, Ermera District, Timor Leste. Primary and secondary data were collected in this research. Respondents were selected by stratified random sampling method. Financial feasibility study on coffee farming were analyzed by using Net Present Value (NPV), Internal Rate of Return (IRR) dan Net Benefit Cost Ratio (NBCR). Rank Spearman test was used to analyze the correlation between productivity with variable of production factors and socioeconomic characteristics of farmers. The results showed that Arabica coffee farming was financially feasible to be develop with NPV of USD 205,291,130; IRR of 17.449%; and Net B/C ratio of 2.911 at discount factor 10%. Arabica coffee farming at Poetete Village was classified less responsive toward productivity increasing at 10% and price decreasing at 10% with NPV of USD 37,367,151; IRR of 25.95%; and Net B/ C ratio of 3.862 at discount factor 1%. The correlation between productivity with land ownership (0.965), experience of farmers (0.613), age of farmers (0.663), farmers education level (0.748) and household size (0.791) were categorized as strong to very strong.